PROBLEM-BASED LEARNING OF STUDENT WORKSHEETS ON HEAT TRANSFER MATERIALS IN ELEMENTARY SCHOOL - Anggraini, Dian Mustika; Nisak, Nanda Amilia Dwi Choirun (Prodi PGMI STIT Sunan Giri Bima, 2023)
The purpose of this research is to develop student worksheet of Problem Based Learning on heat transfer material in class V SDN Bakalan Krajan 2 Malang which is valid according to material experts and teaching materials experts, practical according to teachers, and interesting according to students. This product can be used as teaching materials and additional aids in KD 3.6 and 4.6 heat transfer materials. This research uses the Research and Development (RnD) method and the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. Data collection techniques used are interviews, observations, and questionnaires. The results of the validation of material experts get an average of 94%, teaching materials experts 95.83%, practicality of student worksheet according to users get 100%, and student responses about the attractiveness of student worksheet each get 100% and 97.67%. Thus, it can be concluded that the PBL-based worksheets on heat transfer material in class V SDN Bakalan Krajan 2 Malang are very valid according to experts, practical according to teachers as users, interesting according to students and suitable for use in the learning process without revision.